The Impact of Energy Cooperation and the Role of the One Belt and Road Initiative in Revolutionizing the Geopolitics of Energy among Regional Economic Powers: An Analysis of Infrastructure Development and Project Management. (12th October 2020) - Hao, Wu; Shah, Syed Mehmood Ali; Nawaz, Ahsan; Asad, Ali; Iqbal, Shahid; Zahoor, Hafiz; Maqsoom, Ahsen
Abstract : This paper examines how the latest mega plan and the Belt and Road Initiative (BRI) will impact the geopolitics of energy and infrastructural development. With a massive change in the supply and demand of global energy and its infrastructure, the transition of international energy order is in the making. While the US is going towards a more isolationist path from its traditional superpower role, there are rising economies such as China, India, Japan, and Russia which are undoubtedly playing a vital role in the geopolitical stage and the other development endeavors. Several regions such as Central Asia, the Arctic, Eastern Mediterranean, and the South China Sea are offering substantial natural gas and oil reserves and drawing global attention to develop energy cooperation. This situation is profoundly influencing the transition of energy order. In this transition, BRI is supposed to play an important role. As a mega development strategy with a robust geostrategic dimension, it purposes to advocate interconnectivity collaboration in framework, exchange, and advancement among the partaking nations. This super arrangement offers a lot of ventures, foundation developments, and modern reconciliation in the energy sector. The country is trying to establish a multilateral platform for endorsing and shielding energy cooperation under BRI. This paper, therefore, attempts to observe how this mega plan will contribute to reshaping the existing energy order as well as the geopolitics of energy with motivation on multifaceted energy collaboration.